Temperature Acclimation of the Picoalga Ostreococcus tauri Triggers Early Fatty-Acid Variations and Involves a Plastidial ω3-Desaturase - Degraeve-Guilbault, Charlotte; Pankasem, Nattiwong; Gueirrero, Maurean; Lemoigne, Cécile; Domergue, Frédéric; Kotajima, Tomonori; Suzuki, Iwane; Joubès, Jérôme; Corellou, Florence (Frontiers in Plant Science, 2021)
Alteration of fatty-acid unsaturation is a universal response to temperature changes. Marine microalgae display the largest diversity of polyunsaturated fatty-acid (PUFA) whose content notably varies according to temperature. The physiological relevance and the molecular mechanisms underlying these changes are however, still poorly understood. The ancestral green picoalga Ostreococcus tauri displays original lipidic features that combines PUFAs from two distinctive microalgal lineages (Chlorophyceae, Chromista kingdom). In this study, optimized conditions were implemented to unveil early fatty-acid and desaturase transcriptional variations upon chilling and warming. We further functionally characterized the O. tauri ω3-desaturase which is closely related to ω3-desaturases from Chromista species. Our results show that the overall omega-3 to omega-6 ratio is swiftly and reversibly regulated by temperature variations. The proportion of the peculiar 18:5 fatty-acid and temperature are highly and inversely correlated pinpointing the importance of 18:5 temperature-dependent variations across kingdoms. Chilling rapidly and sustainably up-regulated most desaturase genes. Desaturases involved in the regulation of the C18-PUFA pool as well as the Δ5-desaturase appear to be major transcriptional targets. The only ω3-desaturase candidate, related to ω3-desaturases from Chromista species, is localized at chloroplasts in Nicotiana benthamiana and efficiently performs ω3-desaturation of C18-PUFAs in Synechocystis sp. PCC6803. Overexpression in the native host further unveils a broad impact on plastidial and non-plastidial glycerolipids illustrated by the alteration of omega-3/omega-6 ratio in C16-PUFA and VLC-PUFA pools. Global glycerolipid features of the overexpressor recall those of chilling acclimated cells.